2018
DOI: 10.1002/1878-0261.12198
|View full text |Cite
|
Sign up to set email alerts
|

miRNA‐mediated ‘tug‐of‐war’ model reveals ceRNA propensity of genes in cancers

Abstract: Competing endogenous RNA (ceRNA) are transcripts that cross‐regulate each other at the post‐transcriptional level by competing for shared microRNA response elements (MREs). These have been implicated in various biological processes impacting cell‐fate decisions and diseases including cancer. There are several studies that predict possible ceRNA pairs by adopting various machine‐learning and mathematical approaches; however, there is no method that enables us to gauge as well as compare the propensity of the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Previous studies have demonstrated that circRNAs sponge miRNAs via MREs in numerous diseases. This mechanism has also been reported in cancer initiation and progression (19). Accumulating evidence has demonstrated that circRNAs regulate the growth, development and metastasis of BC by acting as miRNA sponges.…”
Section: Introductionsupporting
confidence: 52%
“…Previous studies have demonstrated that circRNAs sponge miRNAs via MREs in numerous diseases. This mechanism has also been reported in cancer initiation and progression (19). Accumulating evidence has demonstrated that circRNAs regulate the growth, development and metastasis of BC by acting as miRNA sponges.…”
Section: Introductionsupporting
confidence: 52%
“…It has been reported that lncRNA could act as competing endogenous RNA (ceRNA) of miRNAs to indirectly regulate gene expression implicated in various biological processes, including cancer [33]. MiR-186 was found to be a target of NNT-AS1 using bioinformatics prediction program and then NNT-AS1 directly binding to miR-186 was verified by luciferase reporter assay and RNA pull down assay.…”
Section: Discussionmentioning
confidence: 99%
“…After obtaining significantly positively correlated lncRNA-mRNA pairs, we adopted a comprehensive computational approach to identify significant ceRNA candidates. 31 Several methods have been used to predict the ceRNA network, such as the hypergeometric test, which predicts the ceRNAs based on the number of common miRNAs binding to mRNA or lncRNA. [32][33][34] These studies considered only a single parameter.…”
Section: Cerna Propensity Score Calculationmentioning
confidence: 99%
“…T A B L E 1 Sample details of five mRNAs, long non-coding RNAs (lncRNAs), and microRNAs (miRNAs) expression data of temozolomideresistant glioblastoma multiforme tissues and cells. 31 we first computed the binding affinity of each mRNA and lncRNA targeted by miRNA with slight modifications without considering the conservation score. We used both miRanda and Targetscan for target prediction, but one of them (miRanda) does not provide a conservation score of target sites.…”
Section: Cerna Propensity Score Calculationmentioning
confidence: 99%